Postmodernist fiction and the imperial theme - Acquarone, Cecilia (2006)
The present paper suggests a review of modern and postmodern epistemology and their respective positions in reference to history and literature. The postmodern will be seen as a reformulation of modern classical realist positions both in the field of art and of history. This revisionist attitude is manifested in the treatment of the theme of Imperialism in the contemporary novels Wide Sargasso Sea by Jean Rhyss, and Cambridge by Caryl Phillips here analysed.